Product analysis and mechanism of toluene degradation by low temperature plasma with single dielectric barrier discharge - Han Fenglei; Li Mengyu; Zhong Huangrong; Li Ting; Li Dandan; Zhou Shuo; Guo Wenwen; Liu Fang (Journal of Saudi Chemical Society, 2020)
A single dielectric barrier discharge (DBD) low-temperature plasma reactor was set up, and toluene was selected as the representative substance for volatile organic compounds (VOCs), to study the reaction products and degradation mechanism of VOCs degradation by low-temperature plasma. Different parameters effect on the concentration of O3 and NOx during the degradation of toluene were studied. The exhaust in the process of toluene degradation was continuously detected and analyzed, and the degradation mechanism of toluene was explored. The results showed that the concentration of O3 increased with the increase of the power density and discharge voltage of the plasma device. However, as the initial concentration of toluene increased, the concentration of O3 basically keep steady. The concentration of NOx in the by-products increased with the discharge voltage, power density, and initial concentration of toluene in the plasma device, and the concentration of NO2 was much higher than the concentration of NO. The degradation process of toluene was detected and analyzed. The results showed that the degradation mechanism of toluene by plasma includes high energy electron bombardment reaction, active radical reaction and ion molecule reaction. Among them, the effect of high-energy electrons on toluene degradation is the largest, followed by the effect of free radicals, in which oxygen radicals participated in the reaction mainly through the formation of C–O bond, CO bond, (CO)–O– bond and –OH radical, while nitrogen radicals participate in the reaction mainly through the formation of C–NH2, (CNH)- bond, C≡N bond and C–NO2 bond. The results can provide some data supports for the study of low-temperature plasma degradation of VOCs.